STIM2 (Stromal Interaction Molecule 2)–Mediated Increase in Resting Cytosolic Free Ca2+ Concentration Stimulates PASMC Proliferation in Pulmonary Arterial Hypertension. Issue 3 (March 2018) - Song, Shanshan; Carr, Shane G.; McDermott, Kimberly M.; Rodriguez, Marisela; Babicheva, Aleksandra; Balistrieri, Angela; Ayon, Ramon J.; Wang, Jian; Makino, Ayako; Yuan, Jason X.-J.
Abstract : An increase in cytosolic free Ca 2+ concentration ([Ca 2+ ]cyt ) in pulmonary artery smooth muscle cells (PASMCs) triggers pulmonary vasoconstriction and stimulates PASMC proliferation leading to vascular wall thickening. Here, we report that STIM2 (stromal interaction molecule 2), a Ca 2+ sensor in the sarcoplasmic reticulum membrane, is required for raising the resting [Ca 2+ ]cyt in PASMCs from patients with pulmonary arterial hypertension (PAH) and activating signaling cascades that stimulate PASMC proliferation and inhibit PASMC apoptosis. Downregulation of STIM2 in PAH-PASMCs reduces the resting [Ca 2+ ]cyt, whereas overexpression of STIM2 in normal PASMCs increases the resting [Ca 2+ ]cyt . The increased resting [Ca 2+ ]cyt in PAH-PASMCs is associated with enhanced phosphorylation (p) of CREB (cAMP response element–binding protein), STAT3 (signal transducer and activator of transcription 3), and AKT, increased NFAT (nuclear factor of activated T-cell) nuclear translocation, and elevated level of Ki67 (a marker of cell proliferation). Furthermore, the STIM2-associated increase in the resting [Ca 2+ ]cyt also upregulates the antiapoptotic protein Bcl-2 in PAH-PASMCs. Downregulation of STIM2 in PAH-PASMCs with siRNA (1) decreases the level of pCREB, pSTAT3, and pAKT and inhibits NFAT nuclear translocation, thereby attenuating proliferation, and (2) decreases Bcl-2, which leads to an increase of apoptosis. In summary, these data indicate that upregulated STIM2 in PAH-PASMCs, by raising the resting [Ca 2+ ]cyt, contributes to enhancing PASMC proliferation by activating the CREB, STAT3, AKT, and NFAT signaling pathways and stimulating PASMC proliferation. The STIM2-associated increase in the resting [Ca 2+ ]cyt is also involved in upregulating Bcl-2 that makes PAH-PASMCs resistant to apoptosis, and thus plays an important role in sustained pulmonary vasoconstriction and excessive pulmonary vascular remodeling in patients with PAH. Abstract : Supplemental Digital Content is available in the text.